Pengaruh Integrasi Teknologi dalam Pembelajaran Terhadap Kompetensi Pedagogi Digital Guru SMP - Rosyidah, Siti; Achmad Supriyanto; Mustiningsih (Kelola: Jurnal Manajemen Pendidikan, 2025)
The demand for digital competence in education is increasing in line with the rapid advancement of technology, requiring teachers to adapt digital tools and platforms in their instructional practices. This study aims to examine the extent to which technology integration in teaching influences the digital pedagogical competence of public junior high school teachers in Probolinggo City. A non-experimental quantitative approach was employed using a survey method. The sample comprised 185 teachers selected through proportionate stratified random sampling from a total population of 334 teachers. The research instrument was a questionnaire with a 4-point Likert scale, which had passed both validity and reliability tests. Data were analyzed using simple linear regression with the aid of SPSS version 27.0. The findings indicate that technology integration in teaching significantly influences teachers’ digital pedagogical competence, with a coefficient of determination (R²) of 0.624. This suggests that 62.4% of the variance in teachers’ digital pedagogical competence can be explained by the variable of technology integration, while the remaining 37.6% is influenced by other factors. These findings confirm that the more effectively teachers utilize technology, the higher their level of digital pedagogical competence. The main conclusion of this study is that technology integration serves as a critical factor in shaping teachers' digital pedagogical competence. The implication is that policy support and continuous training programs are essential to enhance teachers’ capacity to effectively use technology in teaching. Such efforts are vital for realizing an adaptive, relevant, and high-quality educational transformation in the digital era.